PROBLEMATIKA KAWIN PAKSA DAN FAKTOR-FAKTOR PENYEBABNYA - Arif Hariyanto; R. Fakhrurrazi (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2024)
Marriage in Islam is not simply an ordinary contractual or civil relationship, but it has the value of worship, so it needs to be regulated with certain requirements and pillars that must be fulfilled so that the purpose of making marriage legal can be achieved. Marriage is an important thing in Islam, Islam regulates the procedures for family life so that a sakinah, mawaddah warahmah family is formed. Because this is basically the dream and goal of every marriage that takes place. In this modern era, we often hear the word arranged marriage which is usually called forced marriage. Forced marriage in Indonesian comes from two syllables, namely marriage and force. Which means a marriage that has been urged and forced to be united in a holy marriage